SWS-EDITOR: uma ferramenta baseada em serviços para anotação semântica de serviços web restful - SANTANA, Cleber Jorge Lira de (2015)
Web services have enabled organizations to integrate their software applications, enabling the automation of business processes in several areas. However, it is necessary to provide solutions that favor the selection, discovery and integration of Web services at runtime effectively and efficiently. To promote automation in the request, discovery and composition tasks of Web services, some tools propose the realization of semantic annotation; however, they differ with respect to the features offered and the adequacy to the technologies that are W3C recommendations, and the use is restricted to specific environments (i.e. use only on web environment or desktop). The use of services to perform the semantic annotation of Web Services encourages the reuse of the solution in different environments (e.g. desktop, web, mobile) thus enabling to reach a higher number of users. In the current web architecture, many Web services are designed according to the REST architectural style, also known as Restful Web Services based on the HTTP protocol. This paper presents a service-based tool, called SWS Editor (Semantic Web Services Editor) that makes use of OWL ontologies from SAWSDL specification to perform the semantic annotation of Restful Web Services syntactically described in WSDL. The architecture of the proposed tool will enable the creation of a Semantic Web Services repository that can be used for automatic recovery services. As proof of concept, an example of use of the tool is discussed, where its features, service consuming and semantic retrieval via SPARQL queries are presented.